Pengaruh Terapi Relaksasi Islami Terhadap Penurunan Tingkat Nyeri Pada Pasien Post Operasi Fraktur: Literature Review - Syukur Nur Muhammad Daulay; Agustina Retno Hapsari Hapsari; Moebari (Jurnal Indonesia Sehat, 2022)
Background: In developing countries such as Indonesia there are many traffic accidents which is one of the causes of health problems, namely fractures and will cause feelings of discomfort or pain. Medical action performed on fractures is surgical intervention, causing postoperative pain which is classified as acute pain or nociceptive pain. To support the reduction of pain levels with drugs, non-pharmacological therapy was developed as a companion to medical treatment, namely Islamic relaxation therapy. Research Objectives: This study aims to analyze the effect of Islamic relaxation therapy on reducing pain levels in postoperative fracture patients. Methods: Literature review using 2 databases (Google Scholar and Research Gate) to search for journal articles with the criteria for publication in 2011-2020. Results: The results of 5 journals p value <0.05, which means that Islamic relaxation therapy has an influence on the process of reducing postoperative pain levels. Analysis: The effect of Islamic relaxation therapy is able to significantly reduce pain in fracture patients. Conclusion: Based on 5 journals selected according to inclusion criteria, effective in reducing pain in fracture patients by listening to Islamic relaxation therapy in the form of Asmaul Husna and Murottal Quran.